Solid electrolyte material and all-solid-state battery

By adjusting the molar ratios of Li, Zr, X, O and P in solid electrolyte materials, the shortcomings of existing materials in primary charge and discharge efficiency and stability are solved, and efficient solid-state battery performance is achieved.

JP2025054919APending Publication Date: 2025-04-08TDK CORP

Patent Information

Application Number
JP2023164153
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-27
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Existing solid electrolyte materials have shortcomings in improving the efficiency of primary charge and discharge, especially in maintaining high ionic conductivity and stability.

Method used

Solid electrolyte materials with Li, Zr, X, O and P as the main elements are used to ensure the stability and ionic conductivity of the material within a specific range by adjusting the molar ratio of P/Zr, X/Zr, X/P and O/P.

Benefits of technology

A solid-state battery with high primary charge and discharge efficiency has been achieved. By improving the stability and ionic conductivity of solid-state electrolyte materials, the internal resistance is reduced and the overall performance of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025054919000001_ABST
    Figure 2025054919000001_ABST
Patent Text Reader

Abstract

To provide an all-solid-state battery having high initial charge-discharge efficiency.SOLUTION: A solid electrolyte material comprises Li, Zr, X, O, and P, wherein X is one or more elements selected from the group consisting of F, Cl, Br, and I; the molar ratio of P to Zr is 0.05 or more to 1.50 or less; the molar ratio of X to Zr is 5.0 or more to 10.0 or less; the molar ratio of X to P is more than 5.0 and less than 100.0; and the molar ratio of O to P is 0.5 or more to 2.9 or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a solid electrolyte material and an all-solid-state battery. [Background technology]

[0002] In recent years, electronics technology has developed remarkably, and portable electronic devices have become smaller, lighter, thinner, and more multifunctional. Accordingly, there is a strong demand for batteries that serve as the power source for electronic devices to be smaller, lighter, thinner, and more reliable, and all-solid-state batteries that use solid electrolytes as electrolytes have attracted attention. Known solid electrolytes include oxide-based solid electrolytes, sulfide-based solid electrolytes, complex hydride-based solid electrolytes, and halide-based solid electrolytes.

[0003] For example, Patent Documents 1 and 2 disclose halide-based solid electrolytes of a predetermined composition. Patent Documents 3 and 4 disclose halide-based solid electrolytes containing P. Patent Documents 3 and 4 describe that the composition ratio of the solid electrolyte material is set within a predetermined range in order to increase ion conductivity. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2021 / 024783 [Patent Document 2] International Publication No. 2021 / 261558 [Patent Document 3] JP 2006-156284 A [Patent Document 4] International Publication No. 2022 / 091565 Summary of the Invention [Problem to be solved by the invention]

[0005] Halide-based solid electrolytes are said to have higher ionic conductivity than oxide-based solid electrolytes, sulfide-based solid electrolytes, complex hydride-based solid electrolytes, etc. However, it is not enough for a solid electrolyte to only have excellent ionic conductivity. For example, in order to improve the initial charge / discharge efficiency of an all-solid-state battery, the solid electrolyte is required to have high reduction resistance and high stability.

[0006] The present disclosure has been made in consideration of the above problems, and has an object to provide a solid electrolyte material and an all-solid-state battery having high initial charge / discharge efficiency. [Means for solving the problem]

[0007] In order to solve the above problems, the following means are provided.

[0008] (1) A solid electrolyte material according to a first embodiment includes Li, Zr, X, O, and P. X is one or more elements selected from the group consisting of F, Cl, Br, and I. The molar ratio of P to Zr is 0.05 or more and 1.50 or less. The molar ratio of X to Zr is 5.0 or more and 10.0 or less. The molar ratio of X to P is more than 5.0 and less than 100.0. The molar ratio of O to P is 0.5 or more and less than 2.9.

[0009] (2) In the solid electrolyte material according to the above embodiment, the molar ratio of O to P may be 0.5 or more and less than 2.8.

[0010] (3) In the solid electrolyte material according to the above embodiment, the molar ratio of P to Zr may be 0.31 or more and 1.3 or less.

[0011] (4) In the solid electrolyte material according to the above embodiment, the molar ratio of X to Zr may be 5.5 or more and 8.0 or less.

[0012] (5) In the solid electrolyte material according to the above embodiment, the molar ratio of X to P may be 5.1 or more and less than 50.0.

[0013] (6) The solid electrolyte material according to the above aspect may have an X-ray diffraction pattern obtained by X-ray diffraction measurement using Cu-Kα radiation, which has a first peak, a second peak, and a third peak in a diffraction angle range of 28° to 35°. The first peak is a peak whose diffraction intensity is maximum in a diffraction angle range of 29.5°±0.5°, the second peak is a peak whose diffraction intensity is maximum in a diffraction angle range of 31.9°±0.5°, and the third peak is a peak whose diffraction intensity is maximum in a diffraction angle range of 34.6°±0.5°. A first intensity ratio obtained by dividing the diffraction intensity of the second peak by the diffraction intensity of the first peak, and a second intensity ratio obtained by dividing the diffraction intensity of the second peak by the diffraction intensity of the third peak are both less than 2.

[0014] (7) The solid electrolyte material according to the above embodiment may further contain G as an additive element. G is any one or more elements selected from the group consisting of Ba, Ca, Mg, Y, Sr, La, Sc, Yb, Hf, Ce, Ta, Nb, and W, and the molar ratio of G to Zr is 0.5 or less.

[0015] (8) The solid electrolyte material according to the above embodiment may further contain Al as an additive element, and the molar ratio of Al to Zr is 1.6 or less.

[0016] (9) The solid electrolyte material according to the above embodiment may further include a phosphorus compound, in which the total molar ratio of P and O is 90% or more, and the molar ratio of O to P is 0.5 or more and less than 3.0.

[0017] (10) In the solid electrolyte material according to the above aspect, the phosphorus compound may include P2O5.

[0018] (11) The solid electrolyte material according to the above aspect is Li a Zr b G c P d O e X fIt may be represented by. G is any one or more elements selected from the group consisting of Al, Ba, Ca, Mg, Y, Sr, La, Sc, Yb, Hf, Ce, Ta, and Nb. a satisfies 1.0 < a < 5.0. b satisfies 0.5 < b < 1.5. c satisfies c = 0 when G is not included, 0 < c < 1.0 when G is Al, and 0 < c < 0.5 when G is other than Al. d satisfies 0.05 < d < 0.8. e satisfies 0.1 < e < 2.32. f satisfies 4.0 < f < 8.0.

[0019] (12) The all-solid-state battery according to the second aspect includes a positive electrode, a negative electrode, and a solid electrolyte layer sandwiched between the positive electrode and the negative electrode, and the negative electrode contains the solid electrolyte material according to the above aspect.

[0020] (13) The all-solid-state battery according to the third aspect includes a positive electrode, a negative electrode, and a solid electrolyte layer sandwiched between the positive electrode and the negative electrode, and the solid electrolyte layer contains the solid electrolyte material according to the above aspect.

[0021] (14) The all-solid-state battery according to the fourth aspect includes a positive electrode, a negative electrode, and a solid electrolyte layer sandwiched between the positive electrode and the negative electrode, and the positive electrode contains the solid electrolyte material according to the above aspect.

Advantages of the Invention

[0022] The all-solid-state battery according to the above aspect has high initial charge-discharge efficiency.

Brief Description of the Drawings

[0023] [Figure 1] It is a cross-sectional schematic view of the all-solid-state battery according to this embodiment.

Modes for Carrying Out the Invention

[0024] The present embodiment will be described in detail below with reference to the drawings as appropriate. The drawings used in the following description may show characteristic parts in an enlarged scale for the sake of convenience in order to make the features of the present invention easier to understand, and the dimensional ratios of each component may differ from the actual ones. The materials, dimensions, etc. exemplified in the following description are merely examples, and the present invention is not limited thereto, and may be appropriately modified and implemented within the scope of the present invention.

[0025] "Solid electrolyte material" A solid electrolyte material is a substance that can move ions by applying an external electric field. If the ionic conductivity of a solid electrolyte material is high, the transfer of ions in an all-solid-state battery becomes smoother, and the internal resistance becomes smaller. If the stability of a solid electrolyte material is high, the initial charge / discharge efficiency of an all-solid-state battery improves. Solid electrolyte materials can be used as part of the solid electrolyte layer and electrode components of all-solid-state batteries.

[0026] The solid electrolyte material may be in the form of a powder (particles) or in the form of a sintered body obtained by sintering the powder. The solid electrolyte material may be a compact obtained by compressing and molding the powder, a compact obtained by molding a mixture of the powder and a binder, or a coating film formed by applying a coating material containing the powder, a binder, and a solvent, and then removing the solvent by heating. The solid electrolyte material may be crystalline or amorphous.

[0027] The solid electrolyte material according to this embodiment contains Li, Zr, X, O, and P. Li is lithium, Zr is zirconium, X is a halogen, O is oxygen, and P is phosphorus. X is, for example, one or more elements selected from the group consisting of F, Cl, Br, and I.

[0028] The solid electrolyte material according to this embodiment contains Li, Zr, X, O, and P as main elements. The main elements are the major elements confirmed in the composition analysis, excluding the elements mixed as impurities. The main elements are the elements clearly detected in the composition analysis. The composition analysis is performed, for example, by surface analysis using an electron probe microanalyzer (EPMA). The composition analysis may be performed, for example, by energy-dispersive X-ray spectroscopy (TEM-EDS) using a transmission electron microscope or inductively coupled plasma mass spectrometry (ICP-MS). The main elements are, for example, the elements responsible for the crystal structure of the solid electrolyte material. For example, the molar fractions of Li, Zr, X, O, and P are 90% or more of the total number of moles of the solid electrolyte material.

[0029] In the solid electrolyte material according to this embodiment, the molar ratio of P to Zr is 0.05 or more and 1.50 or less, the molar ratio of X to Zr is 5.0 or more and 10.0 or less, the molar ratio of X to P is more than 5.0 and less than 100.0, and the molar ratio of O to P is 0.5 or more and less than 2.9. That is, P / Zr satisfies 0.05 ≤ P / Zr ≤ 1.50, X / Zr satisfies 5.0 ≤ X / Zr ≤ 10.0, X / P satisfies 5.0 < X / P < 100.0, and O / P satisfies 0.5 ≤ O / P < 2.9. When each molar ratio satisfies this range, the solid electrolyte material becomes stable, and the initial charge-discharge efficiency of the all-solid-state battery using this solid electrolyte material is increased.

[0030] The molar ratio of O to P is preferably 0.5 or more and less than 2.8, and more preferably 1.0 or more and less than 2.8. That is, it is preferable that O / P satisfies 0.5 ≤ O / P < 2.8, and more preferable that O / P satisfies 1.0 ≤ O / P < 2.8. Although the reason is not clear, when a predetermined amount of P is contained in the solid electrolyte material, the solid electrolyte material is less likely to be reduced, and the stability of the solid electrolyte material itself is increased. This is presumably because P contained in the solid electrolyte material forms a stable SEI film, increasing the reduction resistance of the solid electrolyte material.

[0031] The molar ratio of P to Zr is preferably 0.31 or more and 1.3 or less, more preferably 0.50 or more and 1.2 or less, and even more preferably 0.5 or more and 1.0 or less. That is, P / Zr preferably satisfies 0.31≦P / Zr≦1.3, more preferably satisfies 0.5≦P / Zr≦1.2, and even more preferably satisfies 0.5≦P / Zr≦1.0. When P / Zr is larger than a predetermined value, a stable SEI film is sufficiently formed during charging and discharging of the all-solid-state battery, and the reduction resistance of the solid electrolyte material is enhanced. Also, when P / Zr is smaller than a predetermined value, the solid electrolyte material exhibits sufficient ion conductivity.

[0032] The molar ratio of X to Zr is preferably 5.5 or more and 8.0 or less. That is, X / Zr preferably satisfies 5.5≦X / Zr≦8.0. When this range is satisfied, the ionic conductivity of the solid electrolyte material is increased, and the initial charge / discharge efficiency is improved.

[0033] The molar ratio of X to P is preferably 5.1 or more and less than 50.0. That is, X / P preferably satisfies 5.1≦X / P≦50.0. When this range is satisfied, the initial charge / discharge efficiency of the solid electrolyte material is increased.

[0034] The contents of Li and Zr in the solid electrolyte material can be determined by high-frequency inductively coupled plasma optical emission spectrometry. For example, iCAP7400 manufactured by ThermoFisher Scientific is an example of an inductively coupled plasma optical emission spectrometry device. The content of X in the solid electrolyte material can be determined by ion chromatography. For example, ICS-2000 manufactured by Dionex is an example of an ion chromatography device. The content of O in the solid electrolyte material can be determined by inert gas fusion-infrared absorption method. For example, EMGA-930 manufactured by Horiba, Ltd. is an example of an oxygen analyzer. The content of P in the solid electrolyte material can be determined by surface analysis using an electron beam microanalyzer (EPMA). The contents of Li, Zr, X, and O in the solid electrolyte material may also be determined using an electron beam microanalyzer (EPMA).

[0035] The solid electrolyte material according to this embodiment may further include an additive element G. The additive element G is any one or more elements selected from the group consisting of Al, Ba, Ca, Mg, Y, Sr, La, Sc, Yb, Hf, Ce, Ta, Nb, and W. When the solid electrolyte material includes the additive element G, the reduction resistance of the solid electrolyte material is further improved, and the initial charge / discharge efficiency of the all-solid-state battery is further improved. When the additive element is Ta or Nb, the ionic conductivity of the solid electrolyte material is improved.

[0036] When the additive element is Al, the molar ratio of Al to Zr is preferably 1.6 or less, more preferably 0.1 to 1.2, and even more preferably 0.1 to 1.0. That is, Al / Zr preferably satisfies Al / Zr≦1.6, more preferably 0.1≦Al / Zr≦1.2, and even more preferably 0.1≦Al / Zr≦1.0. If the amount of the additive element is large, the ionic conductivity of the solid electrolyte material tends to decrease.

[0037] When the additive element is other than Al, the molar ratio of G to Zr is preferably 0.5 or less, more preferably 0.1 to 0.5, and even more preferably 0.1 to 0.3. That is, G / Zr preferably satisfies G / Zr≦0.5, more preferably 0.1≦G / Zr≦0.5, and even more preferably 0.1≦G / Zr≦0.3. If the amount of additive element is large, the ionic conductivity of the solid electrolyte material tends to decrease.

[0038] The solid electrolyte material according to this embodiment includes, for example, a compound represented by the following formula (1). Li a Zr b G c P d O e X f …(1) In formula (1), G is an additive element, X is a halogen, and each corresponds to the above-mentioned ones. a satisfies 1.0 < a < 5.0. b satisfies 0.5 < b < 1.5. c satisfies c = 0 when G is not included, 0 < c < 1.0 when G is Al, and 0 < c < 0.5 when G is other than Al. d satisfies 0.05 < d < 0.8. e satisfies 0.1 < e < 2.32. f satisfies 4.0 < f < 8.0.

[0039] Whether the solid electrolyte material contains the compound of formula (1) can be confirmed by elemental mapping analysis using energy-dispersive X-ray spectroscopy (TEM-EDX) or electron probe microanalyzer (EPMA). In elemental mapping, a region where each constituent element is in a uniform dispersion state can be regarded as a region where the compound represented by formula (1) is synthesized. Note that "each constituent element is in a uniform dispersion state" means that no clear aggregation state is confirmed in elemental mapping.

[0040] P contained in the solid electrolyte material according to this embodiment may be one of the constituent elements of the compound represented by the above formula (1), may be contained as another phosphorus compound different from the compound represented by formula (1), or may be contained as the compound represented by the above formula (1) and a phosphorus compound. When the solid electrolyte material contains another phosphorus compound different from the compound represented by formula (1), a portion where phosphorus has aggregated is confirmed in elemental mapping.

[0041] The phosphorus compound has a total molar ratio of P and O of 90% or more. The phosphorus compound preferably has a molar ratio of O to P of 0.5 or more and less than 3.0, more preferably 1.0 or more and less than 2.8, and is, for example, P2O5. The phosphorus compound exists, for example, as fine particles. The particle size of the fine particles is, for example, 5 μm or less. When the solid electrolyte material contains a phosphorus compound, the moisture resistance of the solid electrolyte material is improved. This phosphorus compound may be a part of the raw materials when synthesizing the solid electrolyte material.

[0042] The X-ray diffraction pattern of the solid electrolyte material according to this embodiment may have a first peak, a second peak, and a third peak in a diffraction angle range of 28° to 35°. The first peak is a peak whose diffraction intensity is maximum in a diffraction angle range of 29.5°±0.5°. The second peak is a peak whose diffraction intensity is maximum in a diffraction angle range of 31.9°±0.5°. The third peak is a peak whose diffraction intensity is maximum in a diffraction angle range of 34.6°±0.5°. The first intensity ratio obtained by dividing the diffraction intensity of the second peak by the diffraction intensity of the first peak and the second intensity ratio obtained by dividing the diffraction intensity of the second peak by the diffraction intensity of the third peak are both preferably less than 2, more preferably 1 or less. When the X-ray diffraction pattern of the solid electrolyte material satisfies this relationship, the reduction resistance of the solid electrolyte material is improved.

[0043] (Method of manufacturing solid electrolyte material) When the solid electrolyte material is in a powder state, it can be produced, for example, by a mechanochemical method. For example, raw material powders containing predetermined elements in a predetermined molar ratio are mixed and reacted. When the solid electrolyte material is in a sintered state, it can be produced, for example, by a solid-phase reaction method. For example, raw material powders containing predetermined elements in a predetermined molar ratio are mixed and molded, and sintered in a vacuum or in an inert gas atmosphere.

[0044] When the raw material powder contains a halide raw material, the halide raw material is likely to evaporate when the temperature is increased. The halogen gas may be made to coexist in the atmosphere during sintering to supplement the halogen. In addition, when the raw material powder contains a halide raw material, sintering may be performed by a hot press method using a mold with high airtightness. In this case, since the mold has high airtightness, evaporation of the halide raw material due to sintering can be suppressed. By sintering in this manner, a solid electrolyte material in the form of a sintered body made of a compound having a predetermined composition is obtained.

[0045] In the manufacturing process of the solid electrolyte material, heat treatment may be performed as necessary. By performing heat treatment, the crystallite size of the solid electrolyte material can be adjusted. For example, in an argon gas atmosphere, heat treatment is preferably performed at a temperature of 130°C to 650°C for 0.5 hours to 60 hours, and more preferably at a temperature of 175°C to 600°C for 1 hour to 30 hours. By performing heat treatment in an argon gas atmosphere at a temperature of 150°C to 550°C for 5 hours to 24 hours, the crystallite size of the solid electrolyte material can be set to 5 nm to 500 nm.

[0046] When the solid electrolyte material contains a phosphorus compound, the phosphorus compound may be added after the solid electrolyte material is synthesized. The synthesis conditions for producing the solid electrolyte material may be changed so that the phosphorus compound remains. For example, when synthesizing the solid electrolyte material by the mechanochemical method or the solid-phase reaction method, a phosphorus-containing raw material is added in a larger amount than desired to proceed with the reaction, so that the phosphorus compound remains in the solid electrolyte material.

[0047] The crystallinity of the solid electrolyte material can be controlled by changing the mixing state of the raw materials when synthesizing the solid electrolyte material. For example, the intensity ratio of the X-ray diffraction pattern can be changed by changing the rotation speed of the planetary ball mill. It is considered that the higher the rotation speed of the planetary ball mill during synthesis, the greater the energy applied to the raw materials, resulting in differences in the crystal structure of the solid electrolyte material. The rotation speed of the planetary ball mill during synthesis is preferably, for example, 250 rpm to 390 rpm.

[0048] The solid electrolyte material according to the present embodiment has high reduction resistance because the molar ratio of Li, Zr, X, O, and P is within a predetermined range. If a large amount of P is added to the raw material when synthesizing the solid electrolyte material, there is a high possibility that P2O5, which has no ion conductivity, will be formed, and it has been thought that P2O5, which has no ion conductivity, will cause the ion conductivity of the solid electrolyte material to decrease. Therefore, the content of P in the solid electrolyte material has tended to be small. However, if the content of P in the solid electrolyte material is within a predetermined range, the ion conductivity does not decrease significantly, and the reduction resistance of the solid electrolyte material is improved. It is considered that the reason why the reduction resistance of the solid electrolyte material is improved is because P contained in the solid electrolyte material forms a stable SEI film. A solid electrolyte material with high reduction resistance is stable even during charging and discharging of an all-solid-state battery, and an all-solid-state battery using a solid electrolyte material with high reduction resistance has good initial charge and discharge efficiency.

[0049] "All-solid-state battery" FIG. 1 is a schematic cross-sectional view of an all-solid-state battery 100 according to this embodiment. The all-solid-state battery 100 shown in FIG. 1 includes a power generating element 40 and an exterior body 50. The exterior body 50 covers the periphery of the power generating element 40. The power generating element 40 is connected to the outside via a pair of terminals 60, 62 connected to the power generating element 40. Although a laminated type battery is shown in FIG. 1, a wound type battery may also be used. The all-solid-state battery 100 is used, for example, in laminate batteries, square batteries, cylindrical batteries, coin batteries, button batteries, etc.

[0050] <Power generation element> The power generating element 40 includes a solid electrolyte layer 10, a positive electrode 20, and a negative electrode 30. The power generating element 40 is charged or discharged by the exchange of ions between the positive electrode 20 and the negative electrode 30 via the solid electrolyte layer 10 and the exchange of electrons via an external circuit.

[0051] (Solid electrolyte layer) The solid electrolyte layer 10 is sandwiched between a positive electrode 20 and a negative electrode 30. The solid electrolyte layer 10 includes a solid electrolyte that can move ions by an externally applied voltage. For example, the solid electrolyte conducts lithium ions and inhibits the movement of electrons.

[0052] The solid electrolyte layer 10 is, for example, a halide-based solid electrolyte. The solid electrolyte layer 10 includes, for example, the above-mentioned solid electrolyte material. When the above-mentioned solid electrolyte material is included in the positive electrode 1 or the negative electrode 2, the solid electrolyte material included in the solid electrolyte layer 3 does not have to be the above-mentioned one.

[0053] The solid electrolyte layer 3 may contain, in addition to the solid electrolyte, a binder, a compound, etc. The binder may be the same as that used in the positive electrode 1 or the negative electrode 2. The compound is a material originating from the raw material powder.

[0054] (positive electrode) 1, the positive electrode 20 has a plate-shaped (foil-shaped) positive electrode collector 22 and a positive electrode active material layer 24. The positive electrode active material layer 24 is in contact with at least one surface of the positive electrode collector 22.

[0055] The positive electrode current collector 22 may be made of any electronically conductive material that is resistant to oxidation during charging and is not easily corroded. The positive electrode current collector 22 may be made of, for example, a metal such as aluminum, stainless steel, nickel, or titanium, or a conductive resin. The positive electrode current collector 22 may be in the form of a powder, a foil, a punched piece, or an expanded piece.

[0056] The positive electrode active material layer 24 contains a positive electrode active material, and optionally a solid electrolyte, a binder, and a conductive assistant.

[0057] The positive electrode active material is not particularly limited as long as it can reversibly absorb and release, and insert and remove (intercalate and deintercalate) lithium ions, and any positive electrode active material used in known all-solid-state batteries can be used. Examples of the positive electrode active material include lithium-containing metal oxides and lithium-containing metal phosphates.

[0058] Lithium-containing metal oxides include, for example, lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese spinel (LiMn2O4), and lithium manganese oxides represented by the general formula: LiNi x Coy Mn z O2 (x+y+z=1), lithium vanadium compounds (LiVOPO4, Li3V2(PO4)3), olivine-type LiMPO4 (where M represents at least one selected from Co, Ni, Mn, and Fe), lithium titanate (Li4Ti5O 12 ) etc.

[0059] The positive electrode active material may not contain lithium. Examples of such positive electrode active materials include non-lithium-containing metal oxides (MnO2, V2O5, etc.), non-lithium-containing metal sulfides (MoS2, etc.), and non-lithium-containing fluorides (FeF3, VF3, etc.). When using a positive electrode active material that does not contain lithium, the negative electrode is doped with lithium ions in advance, or a negative electrode containing lithium ions is used.

[0060] The positive electrode active material layer 24 may contain a solid electrolyte material. The solid electrolyte material is, for example, the above-mentioned solid electrolyte material. When the above-mentioned solid electrolyte material is used for the negative electrode 2 or the solid electrolyte layer 3, the solid electrolyte material of the positive electrode 1 does not have to be the above-mentioned solid electrolyte material. The solid electrolyte material contained in the positive electrode active material layer 24 is, for example, the same as the solid electrolyte material contained in the solid electrolyte layer 10. When the solid electrolyte material contained in the solid electrolyte layer 10, the positive electrode 20, and the negative electrode 30 is the same, the all-solid-state battery 100 can be easily manufactured.

[0061] The content of the solid electrolyte in the positive electrode active material layer 24 is not particularly limited, but is preferably from 1 mass % to 50 mass %, and more preferably from 5 mass % to 30 mass %, based on the total mass of the positive electrode active material, the solid electrolyte, the conductive assistant, and the binder.

[0062] The positive electrode active material layer 24 may contain a binder. The binder bonds the positive electrode active material, the solid electrolyte material, and the conductive assistant to one another in the positive electrode active material layer 24, and also firmly bonds the positive electrode active material layer 24 to the positive electrode current collector 22. The positive electrode active material layer 24 preferably contains a binder. The binder preferably has oxidation resistance and good adhesiveness.

[0063] Examples of the binder used in the positive electrode active material layer 24 include polyvinylidene fluoride (PVDF) or its copolymer, polytetrafluoroethylene (PTFE), polyamide (PA), polyimide (PI), polyamideimide (PAI), polybenzimidazole (PBI), polyethersulfone (PES), polyacrylic acid (PA) and its copolymer, metal ion crosslinked polyacrylic acid (PA) and its copolymer, polypropylene (PP) grafted with maleic anhydride, polyethylene (PE) grafted with maleic anhydride, and mixtures thereof. Among these, it is particularly preferable to use PVDF as the binder.

[0064] The content of the binder in the positive electrode active material layer 24 is not particularly limited, but is preferably 0.3% by mass to 10% by mass, more preferably 0.3% by mass to 5% by mass, based on the total mass of the positive electrode active material, solid electrolyte, conductive assistant, and binder. If the amount of binder is too small, it tends not to be possible to form a positive electrode 20 with sufficient adhesive strength. Conversely, if the amount of binder is too large, it tends to be difficult to obtain sufficient volume or mass energy density, since general binders are electrochemically inactive and do not contribute to discharge capacity.

[0065] The conductive assistant improves the electronic conductivity of the positive electrode active material layer 24. Known conductive assistants can be used. Examples of the conductive assistant include carbon materials such as carbon black, graphite, carbon nanotubes, and graphene, metals such as aluminum, copper, nickel, stainless steel, iron, and amorphous metals, conductive oxides such as ITO, and mixtures thereof. The conductive assistant may be in the form of powder or fiber.

[0066] There are no particular limitations on the content of the conductive assistant in the positive electrode active material layer 24. When the conductive assistant is added, the mass ratio of the conductive assistant is preferably 0.5 mass % or more and 20 mass % or less, and more preferably 1 mass % to 5 mass %, based on the total mass of the positive electrode active material, solid electrolyte, conductive assistant, and binder.

[0067] (Negative electrode) 1, the negative electrode 30 has a negative electrode current collector 32 and a negative electrode active material layer 34. The negative electrode active material layer 34 is in contact with the negative electrode current collector 32. The negative electrode active material layer 34 is located between the negative electrode current collector 32 and the solid electrolyte layer 10.

[0068] The negative electrode current collector 32 may have electronic conductivity. The negative electrode current collector 32 is made of, for example, a metal such as copper, aluminum, nickel, stainless steel, or iron, or a conductive resin. The negative electrode current collector 32 may be in the form of a powder, a foil, a punching, or an expandable material.

[0069] The negative electrode active material layer 34 contains a negative electrode active material, and optionally a solid electrolyte, a binder, and a conductive assistant.

[0070] The negative electrode active material is not particularly limited as long as it can reversibly absorb and release lithium ions and insert and remove lithium ions. The negative electrode active material may be any negative electrode active material used in known all-solid-state batteries. The negative electrode active material layer 34 may contain, for example, lithium metal as the negative electrode active material, or may contain at least one selected from graphite, silicon, and tin.

[0071] Alternatively, the negative electrode 30 may have only the negative electrode current collector 32, with lithium metal being deposited between the negative electrode current collector 32 and the solid electrolyte layer 10 during charging, and the lithium metal being dissolved during discharging.

[0072] The negative electrode active material layer 34 may contain a solid electrolyte material. The solid electrolyte material is, for example, the solid electrolyte material described above. When the above-mentioned solid electrolyte material is used for the positive electrode 1 or the solid electrolyte layer 3, the solid electrolyte material of the negative electrode 30 does not have to be the above-mentioned solid electrolyte material. The content of the solid electrolyte material is not particularly limited, but is preferably 1 vol.% or more and 50 vol.% or less, and more preferably 5 vol.% or more and 30 vol.% or less, based on the total mass of the negative electrode active material, the solid electrolyte material, the conductive assistant, and the binder.

[0073] The binder and conductive assistant contained in the negative electrode 30 are the same as the binder and conductive assistant contained in the positive electrode 20 .

[0074] <Exterior body> The exterior body 50 houses the power generating element 40 therein. The exterior body 50 prevents moisture and the like from entering from the outside to the inside. As shown in Fig. 1, for example, the exterior body 50 has a metal foil 52 and a resin layer 54 laminated on each side of the metal foil 52. The exterior body 50 is a metal laminate film in which the metal foil 52 is coated with the resin layer 54 from both sides.

[0075] The metal foil 52 is, for example, an aluminum foil or a stainless steel foil. The resin layer 54 can be, for example, a resin film such as polypropylene. The materials constituting the resin layer 54 may be different between the inside and outside. For example, the outside material can be a polymer with a high melting point, such as polyethylene terephthalate (PET) or polyamide (PA), and the inside material can be polyethylene (PE) or polypropylene (PP).

[0076] <Terminal> The terminals 60 and 62 are connected to the negative electrode 30 and the positive electrode 20, respectively. The terminal 62 connected to the positive electrode 20 is a positive electrode terminal, and the terminal 60 connected to the negative electrode 30 is a negative electrode terminal. The terminals 60 and 62 are responsible for electrical connection to the outside. The terminals 60 and 62 are made of a conductive material such as aluminum, nickel, or copper. The connection method may be welding or screwing. The terminals 60 and 62 are preferably protected with insulating tape to prevent short circuits.

[0077] [Manufacturing method of all-solid-state batteries] The positive electrode is manufactured by applying a paste containing a positive electrode active material onto a positive electrode current collector 22 and drying it to form a positive electrode active material layer 24. The above-mentioned solid electrolyte material may be added to the paste containing the positive electrode active material.

[0078] Next, the negative electrode 30 is prepared. The negative electrode is manufactured by applying a paste containing a negative electrode active material onto a negative electrode current collector 32 and drying it to form a negative electrode active material layer 34. The above-mentioned solid electrolyte material may be added to the paste containing the negative electrode active material.

[0079] The power generating element 40 can be produced, for example, by powder molding. A guide with a hole is placed on the positive electrode 20, and the guide is filled with a solid electrolyte material. The surface of the solid electrolyte material is then smoothed, and the negative electrode 30 is placed on top of the solid electrolyte material. This causes the solid electrolyte material to be sandwiched between the positive electrode 20 and the negative electrode 30. Pressure is then applied to the positive electrode 20 and the negative electrode 30 to pressure mold the solid electrolyte material. By pressure molding, a laminate is obtained in which the positive electrode 20, the solid electrolyte layer 10, and the negative electrode 30 are stacked in this order.

[0080] Next, external terminals are welded to the positive electrode current collector 22 of the positive electrode 20 and the negative electrode current collector 32 of the negative electrode 30, which form the laminate, by a known method, to electrically connect the positive electrode current collector 22 or the negative electrode current collector 32 to the external terminal. Thereafter, the laminate connected to the external terminal is housed in an exterior body 50, and the opening of the exterior body 50 is heat-sealed to seal it. Through the above steps, the all-solid-state battery 100 of this embodiment is obtained.

[0081] The all-solid-state battery 100 according to this embodiment contains the above-mentioned solid electrolyte material in at least one of the positive electrode 20, the negative electrode 30, and the solid electrolyte layer 10. The above-mentioned solid electrolyte material has excellent stability. Therefore, the all-solid-state battery 100 containing the above-mentioned solid electrolyte material has high initial charge / discharge efficiency.

[0082] The above describes the embodiments of the present invention in detail with reference to the drawings. However, each configuration and combination thereof in each embodiment is merely an example, and addition, omission, substitution, and other modifications of the configuration are possible without departing from the spirit of the present invention. EXAMPLES

[0083] "Example 1" ZrCl4, LiCl, and P2O5 were weighed in a predetermined molar ratio in a glove box with a dew point of about -75°C. Next, the raw material powder was put into a zirconia sealed container for a planetary ball mill, which had zirconia balls of 5 mmΦ in advance. Next, the sealed container was covered, the lid was screwed onto the container body, and the space between the lid and the container was sealed with polyimide tape. The polyimide tape has the effect of blocking moisture. Next, the zirconia sealed container was set in the planetary ball mill. The rotation speed was set to 250 rpm, the revolution speed was set to 250 rpm, and the rotation direction and the revolution direction were set in the opposite directions, and a mechanochemical reaction was performed for 24 hours. The solid electrolyte material thus prepared was then subjected to a composition analysis by surface analysis using an electron beam microanalyzer (EPMA) to confirm the composition of the solid electrolyte material. As a result, a compound represented by formula (1) was synthesized as the solid electrolyte material.

[0084] [Measurement of ionic conductivity] Next, in a glove box with argon gas circulating at a dew point of approximately -70°C, the solid electrolyte powder was filled into a pressure molding die and pressure molded under a load of approximately 30 KN to prepare a measurement cell for ionic conductivity.

[0085] The pressure molding die is composed of a PEEK (polyether ether ketone) cylinder with a diameter of 10 mm, and upper and lower punches made of SKD11 material with a diameter of 9.99 mm.

[0086] After that, a stainless steel disk and a Teflon (registered trademark) disk, both 50 mm in diameter and 5 mm thick with four screw holes, were prepared and the pressure molding die was set as follows. They were loaded in the following order: stainless steel disk / Teflon (registered trademark) disk / pressure molding die / Teflon (registered trademark) disk / stainless steel disk, and the four screws were tightened with a torque of approximately 3 N m. Screws were also inserted into the screw holes on the sides of the upper and lower punches to serve as external connection terminals.

[0087] The external connection terminal was connected to a potentiostat (VersaSTAT3 manufactured by Princeton Applied Research) equipped with a frequency response analyzer, and the ionic conductivity was measured using an impedance measurement method. Measurement was performed at a measurement frequency range of 1 MHz to 0.1 Hz, an amplitude of 10 mV, and a temperature of 25°C. The ionic conductivity of the solid electrolyte of Example 1 was 0.95 mS / cm.

[0088] [Charge / discharge evaluation] Charge and discharge evaluation was performed for the negative electrode half-cell and the full cell. Two types of negative electrode half-cells were fabricated: the first negative electrode half-cell and the second negative electrode half-cell.

[0089] The first negative electrode half cell was fabricated by the following procedure. In a glove box, 30 mg of the first solid electrolyte material was pressed at a pressure of 0.6 tons for 1 minute. The first solid electrolyte material was LPSC (Li6PS5Cl). Then, 50 mg of the second solid electrolyte material was added to one side of the pressed first solid electrolyte material, and pressed at a pressure of 0.6 tons for 1 minute. The second solid electrolyte material was the solid electrolyte material according to the above-mentioned embodiment. Next, 10 mg of the negative electrode mixture was added to one side of the second solid electrolyte material, and pressed at a pressure of 0.6 tons for 1 minute, and then pressed at a pressure of 3 tons for 1 minute. The negative electrode mixture contains a negative electrode active material, a solid electrolyte material, and a conductive assistant in a ratio of 60 parts by mass:35 parts by mass:5 parts by mass. The negative electrode active material was lithium titanate (Li4Ti5O 12) The solid electrolyte material contained in the negative electrode was the above-mentioned solid electrolyte material. Carbon black was used as the conductive additive. Li foil was placed on the surface of the solid electrolyte layer opposite to the surface on which the negative electrode composite material was laminated. These were restrained at 3 Nm using a restraining jig and sealed in an aluminum pouch with terminals. Using this procedure, a negative electrode half cell for charge / discharge evaluation was produced.

[0090] The second negative half-cell uses lithium titanate (Li4Ti5O 12 The difference from the first negative electrode half-cell is that the ZnO was changed from ZnO to graphite. The other conditions were the same as those for the first negative electrode half-cell.

[0091] The full cell was fabricated by the following procedure. In a glove box, 30 mg of the above solid electrolyte and 50 mg of LPSC (Li6PS5Cl) solid electrolyte were filled in order, and pressed at a pressure of 0.6 tons for 1 minute. Then, a negative electrode composite was added to one side of the pressed solid electrolyte material on the LPSC solid electrolyte side, and pressed at a pressure of 0.6 tons for 1 minute, and then pressed at 3 tons for 1 minute. The negative electrode composite was the same as that of the first negative electrode half cell. Then, a positive electrode composite was added to the surface of the solid electrolyte layer opposite to the surface on which the negative electrode composite was laminated, and pressed at a pressure of 0.6 tons for 1 minute, and then pressed at 3 tons for 1 minute. The positive electrode composite contains a positive electrode active material, a solid electrolyte material, and a conductive assistant in a ratio of 70 parts by mass: 27 parts by mass: 3 parts by mass. The positive electrode active material is lithium cobalt oxide (LiCoO2). The solid electrolyte material contained in the positive electrode was the above-mentioned solid electrolyte material. The conductive assistant was carbon black. They were restrained at 3 Nm using a restraining jig and sealed in an aluminum pouch with terminals. In this way, a full cell for charge / discharge evaluation was produced.

[0092] Next, the first negative electrode half cell, the second negative electrode half cell, and the full cell were each charged and discharged in a temperature environment of 25° C. The charge and discharge rates were set to 0.05C (the current value at which charging or discharging is completed in 20 hours when charging or discharging at a constant current of 1 mA is performed at 25° C.), and a charge and discharge test was performed. Charging was performed at a constant current and constant voltage up to 2.8V, and discharging was performed up to 1.3V.

[0093] "Examples 2 to 14" Examples 2 to 14 differ from Example 1 in that the mixing ratio of the raw materials when forming the solid electrolyte material was changed, and the rotation speed of the planetary ball mill during mixing was changed. The other conditions were the same as in Example 1, and evaluations were performed in the same manner as in Example 1. In Examples 8 to 14, evaluation of the second negative electrode half cell was omitted.

[0094] "Examples 15 to 19" Examples 15 to 19 are different from Example 1 in that a fourth raw material was further added to the raw materials when forming the solid electrolyte material, the mixing ratio of each raw material was changed, and the rotation speed of the planetary ball mill during mixing was changed. In Examples 15 to 17, PCl5 was added as the fourth raw material, in Example 18, Li3PO4 was added as the fourth raw material, and in Example 19, Li2O was added. The other conditions were the same as in Example 1, and evaluations were performed in the same manner as in Example 1. In Examples 15 to 19, evaluation of the second negative electrode half cell was omitted.

[0095] "Examples 20 to 21" Examples 20 to 21 differ from Example 1 in that the raw materials for forming the solid electrolyte material were ZrCl4, LiCl, LiPF6, and LiPO3, and the rotation speed of the planetary ball mill during mixing was changed. The solid electrolyte material contained Cl and F as halogens. The other conditions were the same as in Example 1, and evaluations were performed in the same manner as in Example 1. In Examples 20 and 21, evaluation of the second negative electrode half cell was omitted.

[0096] "Examples 22 to 38" Examples 22 to 38 differ from Example 1 in that a fourth raw material was further added to the raw materials used to form the solid electrolyte material, the mixing ratio of each raw material was changed, and the rotation speed of the planetary ball mill during mixing was changed. The raw material added as the fourth raw material in Examples 22 to 38 is summarized in the table. The other conditions were the same as in Example 1, and evaluations were performed in the same manner as in Example 1. In Examples 22 to 38, evaluation of the second negative electrode half cell was omitted.

[0097] "Examples 39 to 41" Examples 39 to 41 are different from Example 1 in that the mixing ratio of the raw materials when forming the solid electrolyte material was changed, the rotation speed of the planetary ball mill when mixing was changed, and a lithium compound was added. In Examples 39 to 41, when the solid electrolyte material was evaluated, portions where phosphorus was aggregated were confirmed. That is, the solid electrolyte material contains a compound represented by formula (1) and a phosphorus compound. The phosphorus compound of Example 39 had a total molar ratio of P and O of 92%, a molar ratio of O to P of 2.8, and a particle size of 3.0 μm. The phosphorus compound of Example 40 had a total molar ratio of P and O of 93%, a molar ratio of O to P of 1.9, and a particle size of 3.0 μm. The phosphorus compound of Example 41 had a total molar ratio of P and O of 100%, a molar ratio of O to P of 2.5, and a particle size of 2.5 μm. The phosphorus compound of Example 41 was P2O5. The other conditions were the same as in Example 1, and evaluations were performed in the same manner as in Example 1. In Examples 39 to 41, evaluation of the second negative electrode half-cell was omitted.

[0098] "Comparative Example 1" Comparative Example 1 differs from Example 1 in that P2O5 was omitted from the raw materials used in forming the solid electrolyte material. The other conditions were the same as in Example 1, and the same evaluation as in Example 1 was performed.

[0099] "Comparative Examples 2 to 10" Comparative Examples 2 to 10 differ from Example 1 in that the types and mixing ratios of raw materials used in forming the solid electrolyte material were changed. Other conditions were the same as in Example 1, and evaluations were performed in the same manner as in Example 1. Note that some evaluations were omitted in Comparative Examples 2 to 10.

[0100] The following table summarizes the results of Examples 1 to 41 and Comparative Examples 1 to 10. In the following table, I2 / I1 is the first intensity ratio, I3 / I2 is the second intensity ratio, "◯" indicates that a phosphorus compound is contained, "×" indicates that a phosphorus compound is not contained, and "ND" indicates that the ionic conductivity was too low to be measured.

[0101] [Table 1]

[0102] [Table 2]

[0103] [Table 3]

[0104] [Table 4]

[0105] [Table 5]

[0106] [Table 6]

[0107] As shown in Tables 1 to 6, Comparative Examples 1 to 10, in which X / P or O / P did not satisfy the predetermined range, had low initial charge / discharge efficiency. When X / P or O / P was large, i.e., the abundance ratio of P was low, a good SEI film was not formed and the solid electrolyte material was reduced, which is thought to be the reason for the low initial charge / discharge efficiency. When X / P or O / P was small, i.e., the abundance ratio of P was high, a good SEI film was not formed, and the initial charge / discharge efficiency was low, although the reason has not been clearly clarified. [Explanation of symbols]

[0108] 10...solid electrolyte layer, 20...positive electrode, 22...positive electrode current collector, 24...positive electrode active material layer, 30...negative electrode, 32...negative electrode current collector, 34...negative electrode active material layer, 40...power generating element, 50...exterior body, 52...metal foil, 54...resin layer, 60, 62...terminal, 100...all-solid-state battery

Claims

1. Contains Li, Zr, X, O and P; X is one or more elements selected from the group consisting of F, Cl, Br, and I; The molar ratio of P to Zr is 0.05 or more and 1.50 or less, The molar ratio of X to Zr is 5.0 or more and 10.0 or less; the molar ratio of X to P is greater than 5.0 and less than 100.0; A solid electrolyte material having a molar ratio of O to P of 0.5 or more and less than 2.

9.

2. The solid electrolyte material according to claim 1 , wherein a molar ratio of O to P is 0.5 or more and less than 2.

8.

3. The solid electrolyte material according to claim 1 , wherein a molar ratio of P to Zr is 0.31 or more and 1.3 or less.

4. The solid electrolyte material according to claim 1 , wherein a molar ratio of X to Zr is 5.5 or more and 8.0 or less.

5. The solid electrolyte material according to claim 1 , wherein a molar ratio of X to P is 5.1 or more and less than 50.

0.

6. an X-ray diffraction pattern obtained by X-ray diffraction measurement using Cu-Kα radiation has a first peak, a second peak, and a third peak in a diffraction angle range of 28° or more and 35° or less; The first peak is a peak whose diffraction intensity is maximum in a diffraction angle range of 29.5°±0.5°, The second peak is a peak whose diffraction intensity is maximum in a diffraction angle range of 31.9°±0.5°, The third peak is a peak whose diffraction intensity is maximum in a diffraction angle range of 34.6°±0.5°, 2. The solid electrolyte material according to claim 1, wherein a first intensity ratio obtained by dividing the diffraction intensity of the second peak by the diffraction intensity of the first peak and a second intensity ratio obtained by dividing the diffraction intensity of the second peak by the diffraction intensity of the third peak are both less than 2.

7. Further containing G as an additive element, G is at least one element selected from the group consisting of Ba, Ca, Mg, Y, Sr, La, Sc, Yb, Hf, Ce, Ta, Nb, and W; The solid electrolyte material according to claim 1 , wherein a molar ratio of G to Zr is 0.5 or less.

8. Further containing Al as an additive element, The solid electrolyte material according to claim 1 , wherein a molar ratio of Al to Zr is 1.6 or less.

9. Further comprising a phosphorus compound, The phosphorus compound has a total molar ratio of P and O of 90% or more, The solid electrolyte material according to claim 1 , wherein the phosphorus compound has a molar ratio of O to P of 0.5 or more and less than 3.

0.

10. The phosphorus compound is P 2 O 5 The solid electrolyte material according to claim 9 , comprising:

11. Li a Zr b G c P d O e X f It is written as G is one or more elements selected from the group consisting of Al, Ba, Ca, Mg, Y, Sr, La, Sc, Yb, Hf, Ce, Ta, Nb, and W; a satisfies 1.0<a<5.0, b satisfies 0.5<b<1.5, c satisfies c=0 when G is not included, satisfies 0<c<1.0 when G is Al, and satisfies 0<c<0.5 when G is other than Al; d satisfies 0.05<d<0.8, e satisfies 0.1<e<2.32, The solid electrolyte material according to claim 1 , wherein f satisfies 4.0<f<8.

0.

12. A positive electrode, a negative electrode, and a solid electrolyte layer sandwiched between the positive electrode and the negative electrode, The negative electrode comprises the solid electrolyte material according to any one of claims 1 to 11.

13. A positive electrode, a negative electrode, and a solid electrolyte layer sandwiched between the positive electrode and the negative electrode, The solid electrolyte layer comprises the solid electrolyte material according to any one of claims 1 to 11.

14. A positive electrode, a negative electrode, and a solid electrolyte layer sandwiched between the positive electrode and the negative electrode, The positive electrode comprises the solid electrolyte material according to any one of claims 1 to 11.

Citation Information

Patent Citations

  • Lithium-ion conductor and secondary battery using it

    JP2006156284A

  • Solid electrolyte, solid electrolyte layer, and solid electrolyte battery

    WO2021024783A1

  • Solid electrolyte and solid electrolyte battery

    WO2021261558A1

  • Solid electrolyte material, and battery using same

    WO2022091565A1

Cited By

  • Solid-state battery

    WO2026058641A1